The Impact of GRDP and RWP on Regional Minimum Wage (JEJAK, 2020)
The purpose of this research was to find out the effect of the percentage in development of Pematangsiantar city’s regional minimum wages, and the problem in this study how GRDP and RWP affect on the percentage of development of Regionl Minimum Wage at Pematangsiantar City. The method used was quantitative descriptive analysis. Data analysis used were Classic Assumption Test, Multiple Linear Regression, Correlation Coefficient, Determination, F-test and t-test object on RMW at Pematangsiantar city. Finding of research and results of the study can be summarized as follows: 1). The results of the multiple linear regression analysis test are  that the GRDP and RWP had a positive effect on the RMW of Pematangsiantar City, 2). The results of the correlation coefficient indicate that the GRDP and RWP of Pematangsiantar City on its RMW were at a very strong level, while the coefficient of determination of 67.5%  at high or low of the minimum wages can be explained by the GRDP and RWP, while the remaining  of 32.5% was influenced by other factors which were not included in this study, 3). Hypothesis Test for  F-test indicates that the GRDP and RWP influences significantly on Pematang city’s RMW, and for the t- test indicates that the GRDP and RWP had a positive and significant effect on the RMW in Pematangsiantar City from 2005 to 2018. This means that as the GRDP increases, the value of setting Pematangsiantar City's minimum wage in the following year will also increase, and vice versa. The increase of  laborers/workers demands will affect the standard of regioanalwages that will be determined, this happens  because wages will always adjust to the labor market demand. The stipulation of the minimum wage, it has an impact on GRDP in Pematangsiantar City, because the consumptive rate will be carried out in the place where it gets paid.